Hypervelocity impact performance of aluminum egg-box panel enhanced Whipple shield. (February 2016) - Zhang, Xiaotian; Liu, Tao; Li, Xiaogang; Jia, Guanghui
Abstract: The enhanced Whipple shield is widely used on the space stations against space debris hypervelocity impact. Numerical investigation is conducted in this paper to test the concept of using the egg-box panel as the enhanced layer. Taking the flat panel as the benchmark and then the enhanced flat panel is substituted with the egg-box panel. For objective comparison all the egg-box panels have the same areal density as the benchmark flat panel. The performance is tested from the aspects of impact area, cell size and the axial offset, etc. The egg-box panel absorbs more incoming debris energy and generates less large fragments from itself. It can be fabricated by the stamping and forming of the aluminum flat sheet, the cost of manufacture would not be significantly increased. The egg-box panel has better performance than the flat panel and is appropriate to be the enhanced layer of the Whipple shield. Highlights: Egg-box panel stuffed Whipple shield is studied in this manuscript. The performance is tested from: impact area, cell size and the axial offset etc. Analysis and comparisons are made with the unified areal density.